PEA3 is a nuclear target for transcription activation by non-nuclear oncogenes. - Wasylyk, C (1989)
We have found that the activity of the transcription factor PEA3 is regulated by the expression of non-nuclear oncogenes. This factor, although distinct from PEA1 (AP1), is activated by the same oncogenes (v-src, polyoma (Py) middle T, c-Ha-ras, v-mos, v-raf), by tetradecanoyl phorbol-acetate (TPA) and by serum components. We present evidence that PEA3 and PEA1 co-operate in the response of the polyoma virus (Py) alpha domain to oncogene expression. However, in contrast to PEA1, c-fos does not appear to be necessary for activation of PEA3, suggesting that PEA3 is a fos independent target for regulation of transcription by non-nuclear oncogenes.